Light governs asexual differentiation in the grey mould fungus Botrytis cinerea via the putative transcription factor BcLTF2. (18th July 2016) - Cohrs, Kim C.; Simon, Adeline; Viaud, Muriel; Schumacher, Julia
Summary: Botrytis cinerea is a plant pathogenic fungus known for its utilization of light as environmental cue to regulate asexual differentiation: conidia are formed in the light, while sclerotia are formed in the dark. As no orthologues of known regulators of conidiation (e.g., Aspergillus nidulans BrlA, Neurospora crassa FL) exist in the Leotiomycetes, we initiated a de novo approach to identify the functional counterpart in B. cinerea . The search revealed the light‐responsive C2H2 transcription factor BcLTF2 whose expression – usually restricted to light conditions – is necessary and sufficient to induce conidiation and simultaneously to suppress sclerotial development. Light‐induced expression of bcltf2 is mediated via a so far unknown pathway, and is attenuated in a (blue) light‐dependent fashion by the White Collar complex, BcLTF1 and the VELVET complex. Mutation of either component leads to increased bcltf2 expression and causes light‐independent conidiation ( always conidia phenotype). Hence, the tight regulation of bcltf2 governs the balance between vegetative growth that allows for the colonization of the substrate and subsequent reproduction via conidia in the light. The orthologue ssltf2 in the closely related species Sclerotinia sclerotiorum is not significantly expressed suggesting that its deregulation may cause the lack of the conidiation program in this fungus.